PRINSIP BUSINESS JUDGMENT RULE BAGI DIREKSI BADAN USAHA MILIK NEGARA: PRINCIPLES OF BUSINESS JUDGMENT RULE FOR DIRECTORS OF STATE OWNED ENTERPRISES - Muhammad Haris Ersya (Fakultas Hukum Universitas Islam Indragiri, 2023)
The Business Judgment Rule is a doctrine that protects the board of directors against any business decisions that cause losses to the company. The Board of Directors as one of the components participating in the management of BUMN is responsible for managing BUMN for the interests and objectives of BUMN. This study examines criminal liability on the principles of the Business Judgment Rule for Directors of State-Owned Enterprises. The research method used by the author is descriptive research with a normative juridical approach. The results of research conducted by the author can be concluded that the principle of the Business Judgment Rule in Indonesia is a doctrine of protection for directors from accountability for their actions in managing the company. Furthermore, the criminal responsibility of the Directors of BUMN in criminal acts for the actions of the Business Judgment Rule can be applied if it is proven that they have abused their authority which is contrary to laws and regulations and the directors are personally responsible if in carrying out actions on behalf of the company, they are proven guilty or negligent in carrying out their duties management of the company and violating the company's articles of association.